Contribution of Endocrinology - Calderón V., Rolando (2015)
Endocrinology is particularly important how they relate to each other the different parts of the system, which is why when assessing a patient with an endocrine dysfunction must keep in mind the concept of the concert there are between the various endocrine glands, that justifies within this symposium before speaking of functional ovarian exploration say something functional exploration of other endocrine glands closely related to it, both for its direct dependence as in the case of pituitary disorders as because they can affect the function ovarian.